2015
DOI: 10.1093/migration/mnv019
|View full text |Cite
|
Sign up to set email alerts
|

The politics of trans-national belonging: A study of the experiences of second-generation Egyptians during a period of socio-political change in Egypt

Abstract: intersections of gender, religion, class and nationality sometimes constrain these activities. In the process, attention is drawn to the hierarchies of belonging that structure trans-national fields and the degree to which struggles for recognition and status are shaped by the demands of host populations, notably during periods when social identities come under sustained scrutiny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This article has contributed to scholarship on second-generation migrants, particularly on their 'visibility' and return mobilities. Our research confirmed the findings of Saey and Skey (2016), with regard to Muslim identities after 9/11, that 'criticial' historical events can give new meaning and content to the experience of being a second-generation migrant. EU Enlargement and the politics leading up to the Brexit referendum were events which suddenly made Poles highly visible in the UK, and this exposure also affected British-born Poles.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This article has contributed to scholarship on second-generation migrants, particularly on their 'visibility' and return mobilities. Our research confirmed the findings of Saey and Skey (2016), with regard to Muslim identities after 9/11, that 'criticial' historical events can give new meaning and content to the experience of being a second-generation migrant. EU Enlargement and the politics leading up to the Brexit referendum were events which suddenly made Poles highly visible in the UK, and this exposure also affected British-born Poles.…”
Section: Discussionsupporting
confidence: 88%
“…The concept of integration is apt because it implies becoming part of a whole, an aspiration which, we shall argue, was partly motivating our interviewees. The aspiration to 'belong' is noted by other researchers of the second generation, for example King and Christou (2014) and Saey and Skey (2016). Finally, 'integrate' is both a transitive verb (taking a direct object) and an intransitive one.…”
Section: Literature and Concepts: Generation Wave And Integrationmentioning
confidence: 78%
See 1 more Smart Citation
“…It also highlights the importance of cyberactivism in the case of women's and young people's transnational participation. Sarah Saey and Michael Skey (2015) have examined the political participation of second generation Egyptians in the revolution and subsequent events in Egypt. They highlight the shifting sense of belonging that these youths, originally residing the US, displayed as the protests descended into a spiral of violence and were ended by a reinstated authoritarian system.…”
Section: The Research On the Impact And Reception Of The Arab Uprisinmentioning
confidence: 99%
“…The line between being ‘too American’ and ‘too Indian’ is never clear.” The notion of in-betweenness is often used to describe how second-generation migrants straddle between two worlds without necessarily feeling completely at home or welcome in either of them—a dynamic shown among, for instance, American-Egyptians. Saey and Skey ( 2016 ) found that, while this ambiguous identity can be troubling, second-generation migrants “returning” to Egypt selectively emphasized either their Egyptian or “foreign” identities depending on what helped them most in a particular situation.…”
Section: Introductionmentioning
confidence: 99%